Performance of indigenous bacterial consortia for bioremediation of domestic wastewater - Sukmawati; Birawida, Agus Bintara; Ambeng; Daud, Anwar; Rahim, Irwan Ridwan; Ibrahim, Erniwati; Mohd Sham, Shaharuddin (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2026)
Domestic wastewater pollution poses significant environmental challenges, particularly in small island communities where centralized treatment systems are limited. This study evaluated the performance of an indigenous six-strain bacterial consortium (Aeromonas veronii, Enterobacter sichuanensis, Klebsiella pneumoniae, Bacillus albus, Escherichia fergusonii, and Pseudomonas aeruginosa) for domestic wastewater treatment under controlled laboratory conditions. The consortium was applied at inoculum concentrations of 0%, 5%, 10%, and 15% and incubated for 2–8 days. Removal efficiencies of total suspended solids (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammonia (NH₃), and oil-grease were determined using standard analytical procedures (SNI 2005–2019). Two-way ANOVA indicated that both inoculum concentration and incubation period significantly affected pollutant removal efficiency (p < 0.05). The highest treatment performance was achieved at 15% inoculum after 8 days, with removal efficiencies of 68.75% (TSS), 52.01% (BOD), 42.94% (COD), 80.70% (NH₃), and 98.75% (oil-grease). Removal efficiency increased proportionally with microbial dosage and exposure duration, suggesting cooperative microbial degradation processes. These findings suggest that indigenous multistrain bacterial consortia can serve as a feasible biological alternative for decentralized domestic wastewater treatment systems in small island environments.